2020
DOI: 10.1111/cid.12928
|View full text |Cite
|
Sign up to set email alerts
|

Dental implant‐based oral rehabilitation in patients reconstructed with free fibula flaps: Clinical study with a follow‐up 3 to 6 years

Abstract: Background: Oral rehabilitation of patients after maxillofacial reconstructive surgery represents a challenge and stable prosthetic retention can be achieved with the use of dental implants.Purpose: This retrospective report aimed to evaluate implant-based oral rehabilitation following maxillofacial reconstruction with free fibula flaps.Materials and Methods: A total of 14 patients who had reconstruction with fibula flaps either by CAD/CAM or conventional surgery were included in this study. A total of 56 impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…18 Additionally, dental rehabilitation in free flap patients improves post-operative quality of life and mastication, underscoring the importance of considering dental rehabilitation in pediatric patients. 19,20 Future studies may focus on the implications of flap healing with immediate dental implant placement and rehabilitation. Despite the lack of dental restoration, patients achieved intelligible speech following reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Additionally, dental rehabilitation in free flap patients improves post-operative quality of life and mastication, underscoring the importance of considering dental rehabilitation in pediatric patients. 19,20 Future studies may focus on the implications of flap healing with immediate dental implant placement and rehabilitation. Despite the lack of dental restoration, patients achieved intelligible speech following reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pelligrino in 2018 demonstrated a 95% success rate of dental implant placement into fibula free flaps used for orofacial reconstruction, with a low incidence of complications including implantitis 18 . Additionally, dental rehabilitation in free flap patients improves post‐operative quality of life and mastication, underscoring the importance of considering dental rehabilitation in pediatric patients 19,20 . Future studies may focus on the implications of flap healing with immediate dental implant placement and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Oral rehabilitation success might decrease because of the insu cient retention and stability of the prosthesis. Survival rates of free aps and subsequent implants were reported by various authors with promising results [22,[24][25][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The pre/post-operative and surgical protocol was described in detail in the previous publications by the same team of authors [28,29]. In brief, the rst stage maxillofacial operation was performed simultaneously by two teams.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation